Subaltern groups and linguistic prejudice in the media. An introduction - Fernández-Ulloa, Teresa (Círculo de Lingüística Aplicada a la Comunicación, 2025)
The representation of subaltern groups in the media is governed by stereotyping, which only perpetuates social hierarchies and limits agency. These subaltern groups, marginalized by race, gender, religion, or socioeconomic status, face linguistic prejudice, which is evident both in the terminology and in the biased representation made of them, for example, dehumanizing immigrants, presenting racial minorities in contexts of dependency, stereotyping LGBTQ+ people and religious minorities or victimizing women, which overshadows their strengths and contributions to society. Inclusive and accurate media representation is crucial to challenging these biases, dismantling stereotypes, and promoting equity in societal narratives.